Principles of electromagnetic methods in surface geophysics - Kaufman, Alexander A., 1931-; Alexeev, Dmitri; Oristaglio, Michael L. (Amsterdam ; Waltham, Massachusetts : Elsevier, 2014)
Principles of Electromagnetic Methods in Surface Geophysics contains information about the theory of electromagnetic fields in a conducting media. It describes the theoretical and physical principles of the main geophysical methods using electromagnetic fields, including frequency and transient soundings, electromagnetic profiling, magnetotelluric soundings, high-frequency methods (such as ground-penetrating radar), induction logging in vertical and horizontal boreholes (including measurements while drilling). Special attention is paid to models and signal processing methods used in modern ex.
Print version record.
Keywords: Geophysics -- Methodology; Electromagnetic surface waves; SCIENCE -- Earth Sciences -- General; SCIENCE -- Physics -- Geophysics; Electromagnetic surface waves; Geophysics -- Methodology; Electromagnetic Phenomena; Electronic books